1989
DOI: 10.1007/bf03190836
|View full text |Cite
|
Sign up to set email alerts
|

Mefloquine disposition in normals and in patients with severePlasmodium falciparum malaria

Abstract: Mefloquine pharmacokinetics were studied in Kenyan African normal volunteers and in patients with severe acute attack of Plasmodium falciparum malaria. Peak concentrations were achieved in both groups at 20-24 hours. The mean half-life of elimination was 385 +/- 150 hours (mean +/- SD) in normal subjects while in severe malaria it was 493 +/- 215 hours which was significantly longer (P less than or equal to 0.001). The volume of distribution was significantly smaller in severe malaria where it was 30.76 +/- 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…Karbwang et al [1] found plasma concentrations in healthy Thai volunteers to be twice as high as those reported by Riviere et al [2] in healthy Caucasian volunteers. In contrast, a study by Juma et al [3] [2].…”
contrasting
confidence: 40%
“…Karbwang et al [1] found plasma concentrations in healthy Thai volunteers to be twice as high as those reported by Riviere et al [2] in healthy Caucasian volunteers. In contrast, a study by Juma et al [3] [2].…”
contrasting
confidence: 40%
“…Mean residence times were also very similar to those reported previously; 15.3 (4.7) days compared with 15.5 (3.1) days in Thai adults with uncomplicated malaria (Karbwang et al, 1988a (Karbwang et al, 1988a,b) and are comparable with the estimates in children in this study; mean (s.d.) CLpO 0.52 (0.27) ml kg-' min-', whereas in African adults with more severe malaria (Juma & Ogeto, 1989) estimates were much higher; mean CLp. was 0.89 ml kg-' min-'.…”
Section: Discussionmentioning
confidence: 90%
“…The pharmacokinetic properties of mefloquine have been defined in adults with acute malaria (Juma & Ogeto, 1989;Karbwang et al, 1988a,b;Looareesuwan et al, 1987) but not in children. We have conducted a prospective study of the pharmacokinetic properties of mefloquine in 12 children with acute uncomplicated falciparum malaria living on the Thai-Burmese border.…”
Section: Introductionmentioning
confidence: 99%
“…Because mefloquine is an antimalarial, the in vivo human PK profile is known. Mefloquine and its metabolites are excreted slowly from the body through faeces and urine [38,41] with a terminal elimination half-life of roughly three weeks in healthy subjects, 10 to 14 days in malaria patients with uncomplicated falciparum malaria [42,43] and approximately 20 days in cases involving more severe malaria [43,44]. Its only reported use in veterinary medicine has been as an antimalarial drug for raptors [45].…”
Section: Plos Onementioning
confidence: 99%